Proposing an Algorithm to Solve the Forward and Reverse Logistics Distribution Problem with One Door Container - Stephen Sanjaya Budi; Paulina Kus Ariningsih; Titi Iswari (Jurnal Teknik Industri, 2019)
Forward and reverse logistics are two types of distribution methods that shall be synergized in practices. Two problems in synergizing the two distributions type are (1) how to route vehicles and (2) how to pack the goods inside the vehicle. A truck with only one door for loading and unloading process could create numerous problems of item packing activities. An item picked up from a customer could occasionally block other goods which need to be delivered; hence, the courier shall unload other items before the loading process. This condition will increase the probability of item damage, longer on-loading/off-loading (lo/lo) time, and higher lo/lo cost because of the rapid item movement. Therefore, this article aims to propose an algorithm to solve the problem by creating an algorithm hybrid of routing and packing to find the solution for routing and packing problem, sequentially, with a metaheuristic approach. The proposed method calculates the cost from routing procedure and sum of item movement in every loading and unloading process. Based on the trial on 25 cases, this algorithm generates 59.64% of the containers have zero goods repacking. Several potential future research avenues are also proposed in this article.